LESSONS IN OLD MAN AND THE SEA - Masruddin, Masruddin (Institut Agama Islam Negeri Palopo, 2013)
Â In the novel âThe Old Man and the Seaâ the writer found some positive characters in the novel.Â During the analysis the writer applies structural genetic approach. The analysis shows that Santiago as character who performs spirit, motivation and hard worker. Â Â Then, MandolinÂ shows aÂ helpful character.Â Then the setting of the Novel implies that a man should have a good relation with the nature.Â